Pengaruh Personal Branding dan Self Efficacy terhadap Career Satisfaction melalui Perceived Employability bagi Professional Coach - Hiva Erliani Fitrah; Hardani Widhiastuti (Fakulatas Dakwah IAIN Salatiga, 2022)
Abstract This study aims to analyze the relationship between Personal Branding and Self Efficacy, Perceived employability and career satisfaction. The number of samples taken as many as 60 respondents with purposive sampling technique. Validity test with loading factor and AVE value shows a valid value. The reliability tester with the internal consistency test has Cronbach's Alpha and Composite Reliability values that meet the criteria. The results showed that personal branding the had a positive and significant effect of 1.575 on perceived employability with a P value of 0.000. Self Efficacy has a negative and significant effect of (-0.896) on perceived employability with P-values of 0.037. Personal Branding had positive and significant effect of 0.492 on career satisfaction with P-Value 0.046. Self efficacy had positive and significant effect of 0.393 with P-Value 0.000. Perceived employability not significant affect as moderation for career satisfaction P-value of 03936. AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh personal branding dan self-efficacy terhadap career satisfaction melalaui perceived employability. Jumlah sampel yang diambil sebanyak 60 responden dengan teknik purposive sampling. Uji validitas dengan loading factor dan nilai AVE menunjukkan nilai yang valid. Pengujian reliabilitas dengan uji internal consistency mempunyai nilai Cronbach’s Alpha dan Composite Reliability yang memenuhi kriteria. Hasil penelitian menunjukkan Personal Branding berpengaruh positif 1.575 dan signifikan terhadap perceived employability dengan P-values 0.000. Self-Efficacy berpengaruh negatif (-0.896) dan signifikan terhadap Perceived employability dengan P-values 0.000. Personal Branding berpengaruh positif sebesar 0.492 dan signifikan terhadap career satisfaction dengan P-Value 0.046. Self-Efficacy berpengaruh positif 0.393 dan signifikan terhadap career satisfaction dengan P-Value 0.000. Sedangkan Perceived employabilitity 0.134 tidak berpengaruh signifikan sebagai mediasi terhadap career satisfaction dengan P-Value 0.393. Kata kunci: personal branding; self-efficacy; perceived employability; career satisfaction; professional coach